Pemikiran Fikih Nusantara KH. Sholeh Darat: Studi Kitab Majmu’ah al-Syari’at al-Kafiyat li al-‘Awam Karya KH. Sholeh Darat Semarang - Khakim, Ahmad Lutfi (Lembaga Yasin AlSys, 2026)
Majmūʿah al-Syarīʿāt al-Kāfiyāt li al-ʿAwām is one of the sharīʿah intellectual legacies of the Nusantara, written in Javanese using the Arabic Pegon script by the 18th-century scholar Sholeh ibn Umar al-Samarani (Kyai Sholeh Darat). This article provides a descriptive–analytical examination of the content of the work and its relevance for Nusantara society. The book reflects Kyai Sholeh Darat’s sense of responsibility and concern regarding the religious problems of lay Muslims in his time, particularly in relation to the practice of sharīʿah. Substantively, this work of fiqh emerging from a local community places strong emphasis on the dimension of tasawuf and adopts a contextual fiqh approach that is closely attuned to the community’s socio-religious realities. Analysis of the text shows that although Kyai Sholeh Darat’s fiqh thought does not differ significantly in normative terms from classical fiqh works, it nonetheless represents the rich corpus of Nusantara fiqh that has played an important role in shaping the teachings and traditions of Islam Nusantara. These findings underscore the importance of exploring and developing Nusantara fiqh as a foundation for formulating contextual and moderate Islamic law that is aligned with local traditions and cultures, thereby remaining relevant for regulating the religious life of Muslims in the Nusantara today and in the future.